Can Religious Beliefs be Justified Pragmatically? - McCullagh, C. Behan (Sophia, 2007)
One cannot prove the truth of theological statement, but perhaps one can justify believing them because of the good consequences of doing so. It is irrational to believe statements of which there are good reasons to think false, but those of which there is some, albeit inconclusive, evidence can be believed for pragmatic reasons. However, in the interest of simplicity, it must not be possible to achieve those good consequences without such faith. John Bishop and others have argued that one need only assume theological statements to be true to enjoy the good consequences of a religious life, but in fact, faith is needed for most of these consequences to be achieved.